COMPULSORY ENGLISH ONLINE LEARNING PRACTICES IN SINTANG REGENCY; IMPLEMENTATIONS, CHALLENGES AND POTENTIALS FOR FUTURE IMPROVEMENT - Elfa Sally Lorenza; Dedi Irwan; Ageung Darajat (IKIP PGRI Pontianak, 2024)
This research aims to evaluate online learning practices carried out by schools during the Covid-19 pandemic in SintangRegency. The research implemented a descriptive qualitative approach involving 4 schools spread across Sintang Regency, namely in rural and urban areas. In thiscase, the 4 schools include 2 Junior High Schools and 2 Senior High Schools. The data analysis used in this research is descriptive qualitative, using Thematic Analysis and Cross-case Analysis techniques. The proposed applied direct communication techniques were utilized such tools as interview guidance (open-ended), interview. The results of this study are expected to provide descriptions of the implementation of online learning, the challenges teachers face in designing online learning, and potential improvements that can be made in the future. The research findings indicated that implementation of online learning in Sintangregency have differences, that are in rural schools apply blended learning and urban schools apply fully online learning. In implementing online learning, teachers and students face various challenges, that are teachers are having difficulties in implementing online learning, limited facilities and infrastructure, differences in students' understanding, difficulties of collaboration between parents and students, and issues of motivation in online learners. In further analysis regarding online learning in Sintang Regency, the findings found that the findings found that the potential for future improvements that schools wanted was an evaluation of learning, providing seminar of technology mastery, and synergy of school committees and governments.